1990
DOI: 10.1152/ajpheart.1990.259.2.h324
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system involvement in pressure-overload cardiac hypertrophy in rats

Abstract: We have recently shown that the octapeptide angiotensin II is a potent stimulus of protein synthesis and growth in cultured cardiomyocytes. The present study was performed to determine if the renin-angiotensin system was involved in regulating cardiac cell growth in vivo. The pressure-overload cardiac hypertrophy model that develops in abdominal aorta-constricted rats was studied. At 7 and 15 days after abdominal aorta constriction, rats developed significant left ventricular hypertrophy. The increase in left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
2
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(211 citation statements)
references
References 0 publications
13
192
2
4
Order By: Relevance
“…A growing body of data has suggested that renin-angiotensin system plays an important role in generating cardiac hypertrophy [1][2][3][4][5][6][7]. In the present study, to elucidate the mechanism of the Ang II-induced cardiac hypertrophy, we examined the role of p70 s6K in cultured cardiac myocytes of neonatal rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A growing body of data has suggested that renin-angiotensin system plays an important role in generating cardiac hypertrophy [1][2][3][4][5][6][7]. In the present study, to elucidate the mechanism of the Ang II-induced cardiac hypertrophy, we examined the role of p70 s6K in cultured cardiac myocytes of neonatal rats.…”
Section: Discussionmentioning
confidence: 90%
“…Many lines of evidence have suggested that angiotensin II (Ang II) plays a critical role in inducing cardiac hypertrophy [1][2][3][4][5][6][7]. All components of the renin angiotensin system such as renin, angiotensinogen and angiotensin-converting enzyme (ACE) have been identified in the heart at both mRNA and protein levels [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increase in LV mass produced by abdominal aortic constriction can be completely prevented by an ACE inhibitor without changes in afterload and plasma renin activity. 13 We further investigated the relation between hypertensive cardiac hypertrophy and the cardiac reninangiotensin system. 14 In an in vivo study, spontaneously hypertensive rats (SHR) were assigned to the treatment with a nonpeptide Ang II type 1 receptor antagonist of candesartan or a vasodilating agent of hydralazine.…”
Section: Haemodynamic Overload and The Cardiac Renin-angiotensin Systemmentioning
confidence: 99%
“…7 Increased expression of both cardiac renin mRNA and cardiac angiotensinogen mRNA are seen under conditions of experimental chronic pressure overload in rats. 8,9 Expression of the ACE has also been demonstrated to be upregulated within the myocardium of rats with pressure overload induced LVH. [8][9][10][11] These findings suggest that increased expression of ACE in the presence of increased local production of renin and angiotensinogen produce increases in angiotensin II, as a response to pressure overload or damage, in the left ventricle.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%
“…8,9 Expression of the ACE has also been demonstrated to be upregulated within the myocardium of rats with pressure overload induced LVH. [8][9][10][11] These findings suggest that increased expression of ACE in the presence of increased local production of renin and angiotensinogen produce increases in angiotensin II, as a response to pressure overload or damage, in the left ventricle. 12,13 This activation of the cardiac renin-angiotensin system occurs independently of systemic angiotensin II generation.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%